Identification of the first Toll-like receptor gene in passerine birds: TLR4 orthologue in zebra finch (Taeniopygia guttata) - Vinkler, M; Bryjová, A; Albrecht, T; Bryja, J (Tissue antigens, 2009)
Toll-like receptors (TLRs) are the basic components of the vertebrate pathogen recognition system. Despite uniform general structure, remarkable variability in domain composition can be found in individual TLRs among species. Knowledge of interspecific differences is of particular importance to our understanding of selective pressures on TLRs. Currently, most TLRs are characterized only in a limited number of model species, including domestic chicken as a universal avian model. Here, we describe structure and expression pattern of TLR4 in zebra finch, a widely used passerine model species. The tgTlr4 gene consists of three exons (204, 167 and 3033-3043 bp) that are transcribed into messenger RNA with a relatively long 3'-untranslated region (788 bp). Predicted protein is composed of 842 amino acids (aas) forming extracellular domain with nine leucine-rich repeat (LRR) motives flanked at the carboxy-terminal end by leucine-rich repeat carboxy-terminal domain, transmembrane domain and cytoplasmic toll/interleukin-1 receptor domain. The overall structure is similar to other known TLR4 molecules with 32%-49% aa identity to various mammals and 74% to chicken. Although the position of most of the domains in zebra finch TLR4 resembles their position in chicken, there is one extra LRR at the aa position 207-229 in tgTLR4 and one LRR known in chTLR4 is missing. The gene is highly expressed in the bone marrow and in the spleen, intermediately in the gut and low expression was found in the liver and lungs. For the first time in birds, expression of tgTLR4 in peritoneal macrophages was found to be enhanced by the Escherichia coli lipopolysaccharide treatment.
Keywords: exony; sekvence nukleotidů; Male; Lipopolysaccharides; Protein Structure, Tertiary; toll-like receptor 4; fylogeneze; terciární struktura proteinů; lipopolysacharidy; Exons; peritoneální makrofágy; Phylogeny; molekulární sekvence - údaje; Amino Acid Sequence; mužské pohlaví; jednonukleotidový polymorfismus; sekvenční seřazení; Toll-Like Receptor 4; Animals; Polymorphism, Single Nucleotide; zvířata; sekvence aminokyselin; Passeriformes; Molecular Sequence Data; Base Sequence; Macrophages, Peritoneal; Sequence Alignment